Penguatan Pendidikan Karakter melalui Manajemen Kegiatan Pembiasaan di Lembaga PAUD ANNUR - Mahendra, Deden Deni; Tohidin, Ujang; Komara, Endang; Koswara, Nandang; Helmawati, Helmawati (Universitas Muhammadiyah Magelang, 2025)
Character education serves as a fundamental foundation in shaping children's personalities from an early age. Early Childhood Education (ECE) institutions play a strategic role in instilling character values that are essential for children's future lives. This research is motivated by the need to identify an effective model for strengthening character education through a structured and sustainable approach. One promising approach is the management of habituation activities, which are systematically integrated into children's daily routines within ECE environments. This study focuses on how character education reinforcement can be concretely implemented through the management of habituation activities at PAUD Annur, located in Rengasdengklok Utara Village, Rengasdengklok District, Karawang Regency. A qualitative approach was employed using a case study method. The research subjects included the school principal, teachers, Group B students aged 5–6 years, and parents as supporting participants. Data were collected through participatory observation, in-depth interviews, and documentation of activities. The data analysis was conducted descriptively and qualitatively through data reduction, data presentation, and conclusion drawing, with data validation carried out using source and method triangulation techniques. The findings reveal that habituation activities at PAUD Annur are consistently carried out daily through practices such as performing Dhuha prayers together, reciting prayers before and after learning, singing songs themed around noble morals, greeting teachers and peers, as well as maintaining cleanliness and classroom tidiness. These activities are not merely routines but are managed through systematic planning, implementation, and evaluation by the institution. The management of these habituation activities has proven effective in gradually but significantly nurturing religious character, discipline, responsibility, and social care among children. It can be concluded that the structured and continuous implementation of habituation activity management at PAUD Annur serves as an effective strategy in strengthening character education from an early age. This model can serve as a reference for other ECE institutions in their efforts to shape a young generation that is not only cognitively intelligent but also grounded in strong moral and spiritual values.